Development and validation of the Ulcerative Colitis patient-reported outcomes signs and symptoms (UC-pro/SS) diary - Peter D. R. Higgins; Gale Harding; Dennis A. Revicki; Gary Globe; Donald L. Patrick; Kristina Fitzgerald; Hema Viswanathan; Sarah M. Donelson; Brian G. Ortmeier; Wen Hung Chen; Nancy K. Leidy; Kendra DeBusk (SpringerOpen, 2018)
Abstract Background The clinical course of ulcerative colitis (UC) and the effects of treatment are assessed through patient-reported signs and symptoms (S&S), and endoscopic evidence of inflammation. The Ulcerative Colitis Patient-Reported Outcomes Signs and Symptoms (UC-PRO/SS) measure was developed to standardize the quantification of gastrointestinal S&S of UC in clinical trials through direct report from patient ratings. Design The UC-PRO/SS was developed by collecting data from concept elicitation (focus groups, and individual interviews), then refined through a process of cognitive interviews of 57 UC patients. Measurement properties, including item-level statistics, scaling structure, reliability, and validity, were evaluated in an observational, four-week study of adults with mild to severe UC (N = 200). Results Findings from qualitative focus groups and interviews identified nine symptom items covering bowel and abdominal symptoms. The final UC-PRO/SS daily diary includes two scales: Bowel S&S (six items) and Abdominal Symptoms (three items), each scored separately. Each scale showed evidence of adequate reliability (α = 80 and 0.66, respectively); reproducibility (intraclass correlation coefficient = 0.81, 0.71) and validity, including moderate-to-high correlations with the Partial Mayo Score (0.79; 0.45) and Inflammatory Bowel Disease Questionnaire (IBDQ) total score (− 0.70; − 0.61). Scores discriminated by level of disease severity, as defined by the Partial Mayo Score, Patient Global Rating, and Clinician Global Rating (p < 0.0001). Conclusions Results suggest that the UC-PRO/SS is a reliable and valid measure of gastrointestinal symptom severity in UC patients. Additional longitudinal data are needed to evaluate the ability of the UC-PRO/SS scores to detect responsiveness and inform the selection of responder definitions.